2000
DOI: 10.1681/asn.v11122167
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of ANKRA, a Novel Ankyrin Repeat Protein that Interacts with the Cytoplasmic Domain of Megalin

Abstract: Abstract. Ankyrin-repeat family A protein (ANKRA) is a novel protein that interacts directly and specifically with the cytoplasmic tail of megalin in the yeast two-hybrid system and glutathione-S-transferase pull-down assays. ANKRA has three ankyrin repeats and shows 61% overall homology to regulatory factor X, ankyrin repeat-containing protein. Mapping studies show that the three ankyrin repeats and C-terminus of ANKRA are required for binding to a unique juxtamembrane, 19-amino acid sequence on the megalin t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…The ANKRA2-binding peptide identified in HDAC4 is hydrophobic and contains several leucine and proline residues, which is reminiscent of a previously identified binding region for ANKRA2 on megalin. By means of yeast two-hybrid and glutathione S-transferase (GST)-mediated pull-down assays, Rader et al identified a leucine-and proline-rich, 19-residue fragment (HYRKTGSLLPTLPKLPSLS) from the cytoplasmic tail of megalin that bound to ANKRA2 (10). Therefore, we conclude that the binding sites for ANKRA2 on diverse proteins have related sequences.…”
Section: Resultsmentioning
confidence: 67%
See 3 more Smart Citations
“…The ANKRA2-binding peptide identified in HDAC4 is hydrophobic and contains several leucine and proline residues, which is reminiscent of a previously identified binding region for ANKRA2 on megalin. By means of yeast two-hybrid and glutathione S-transferase (GST)-mediated pull-down assays, Rader et al identified a leucine-and proline-rich, 19-residue fragment (HYRKTGSLLPTLPKLPSLS) from the cytoplasmic tail of megalin that bound to ANKRA2 (10). Therefore, we conclude that the binding sites for ANKRA2 on diverse proteins have related sequences.…”
Section: Resultsmentioning
confidence: 67%
“…Next, we examined whether the binding characteristics of the ANKRA2-HDAC4 complex were maintained in the interaction between ANKRA2 and megalin. The ANKRA2 binding site on megalin has been mapped to a leucine-and proline-rich 19-residue fragment (residues 4448 to 4466: HYRKTGSLLPTLPKLPSLS) (10). Because the ANKRA2-binding site on HDAC4 is formed by a PxLPxI sequence, we inspected the megalin sequence and found that not one but two overlapping PxLPxL motifs are embedded in this small region ( 4458 PTLPKL 4463 and 4461 PKLPSL 4466 , with consensus residues underlined; see Fig.…”
Section: Ankra2 Binds To Hdac4 and Megalin Through A Pxlpxi/l Motifmentioning
confidence: 99%
See 2 more Smart Citations